Indeks Massa Tubuh (IMT) Berkaitan Risiko Jatuh pada Lansia Hipertensi - Ronaldo Ronaldo; Ronasari Mahaji Putri; Hilda Mazarina Devi (Universitas Baiturrahim, 2026)
The problem of hypertension in the elderly continues to increase due to many factors, one of which is being overweight. Overweight can be seen in the Body Mass Index (BMI) value. If the BMI is excessive, it will trigger an imbalance in the body or the risk of falling. The purpose of this study was to determine the relationship between BMI and the risk of falling in elderly people with hypertension at the Husnul Khatimah Elderly Home in Wajak District, Malang Regency. The study design used a cross-sectional approach. The study population consisted of 64 hypertensive elderly individuals, with a sample size of 55 hypertensive elderly individuals selected using simple random sampling. The independent variable was BMI, and the dependent variable was the risk of falling. Data analysis used the Spearman rank test. The results of this study showed that almost half (49.1%) of respondents were overweight according to their BMI; and had a high average risk of falling (63.6%). The Spearman's rank test showed a relationship between BMI and the risk of falling in hypertensive elderly people at the Husnul Khatimah Elderly Home in Wajak District, Malang Regency (p value 0.011; r of 0.339. It is recommended that elderly people lose weight and increase physical activity. Nursing homes should conduct initial BMI screening for elderly residents, and researchers should conduct further studies through health education on BMI management and the risk of falls in elderly people with hypertension.